Metal Allergens of Growing Significance: Epidemiology, Immunotoxicology, Strategies for Testing and Prevention - Forte, Giovanni; Petrucci, Francesco; Bocca, Beatrice (Inflammation & Allergy-Drug Targets (Discontinued), 2008)
Metal-induced allergic contact dermatitis (ACD) is expressed in a wide range of cutaneous reactions following dermal and systemic exposure to products such as cosmetics and tattoos, detergents, jewellery and piercing, leather tanning, articular prostheses and dental implants. Apart from the well known significance of nickel in developing ACD, other metals such as aluminium, beryllium, chromium, cobalt, copper, gold, iridium, mercury, palladium, platinum, rhodium and titanium represented emerging causes of skin hypersensitivity. Despite the European Union directives that limit the total nickel content in jewellery alloys, the water soluble chromium (VI) in cement, and metals banned in cosmetics, the diffusion of metal-induced ACD remained quite high. On this basis, a review on the epidemiology of metal allergens, the types of exposure, the skin penetration, the immune response, and the protein interaction is motivated. Moreover, in vivo and in vitro tests for the identification and potency of skin-sensitizing metals are here reviewed in a risk assessment framework for the protection of consumer's health. Avenues for ACD prevention and therapy such as observance of maximum allowable metal levels, optimization of metallurgic characteristics, efficacy of chelating agents and personal protection are also discussed.
Keywords: Allergic contact dermatitis